TÜRKİYE'DE ÜNİVERSİTE YERLEŞTİRMELERİNDE KONTENJAN KRİZİ: BİLGİSAYAR VE ÖĞRETİM TEKNOLOJİLERİ VE FEN BİLGİSİ ÖĞRETMENLİĞİ. - KILINÇ, Mustafa; SIVACI, Sadık Yüksel; ÇÖPLÜ, Fırat (Mehmet Akif Ersoy University Journal of Education Faculty, 2017)
The purpose of this study is to examine the opinions of the faculty members of the Department of Computer and Instructional Technologies Teaching, Department of Science Teaching, Department of Educational Sciences with respect to the quota status after the 2017 OSYS results. Participants consists of 14 females and 32 males, from the Faculties of Education at Ahi Evran and Mehmet Akif Universities. They are selected through convenience sampling method. To analyze data, content analysis method was used. The opinions of the faculty members regarding the causes of decrease in preference for Computer Education and Instructional Technology and Science Education programs are examined. The main reasons are found and reported as: allowing only first 240.000 candidates to apply these programs, in efficient educational policies and problematical planning in quota, decreased prestige of teaching profession, availability of other options to candidates within 240.000 in admission score type, recent change in admission score type, and low expectations from these departments in terms of finding jobs as teachers.